Edukasi Pemanfaatan Limbah Dapur untuk Pembuatan Eco Enzym - Miftachul Chusnah; Dyah Ayu Sri Hartanti; Siti Nur Qomariyah; Elsa Umi Hanifah; Muhamad Hamdan Syakuro; Nurul Qomariyah; Rifqi Ahmad Asryl Adhim; Salsabila Dinda Khumairoh (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Household waste management is a global problem that urgently must be resolved to ensure environmental sustainability and human health. Organic waste, in particular, is a significant source of waste and is difficult to process efficiently. To overcome this problem, processing waste into eco-enzymes has proven to be the right and efficient solution. To overcome this problem, processing waste into eco-enzymes has proven to be the right and efficient solution. Eco-enzymes are enzymes produced through a biotechnology process with microorganisms to break down organic waste into simpler and environmentally friendly components. The aim of community service activities through training in making eco enzymes from household kitchen waste is to provide innovation to farmers in the form of an alternative to chemical fertilizers. Increasing mothers' knowledge and understanding of technological innovation in making household kitchen waste more effective. The method for this community service activity is Service Learning (SL), including socialization of training on making eco enzymes from kitchen waste and questions and answers from PKK participants in Sidokaton village. Implementation of activities includes initial coordination and permission for service of equipment, provision of tools and materials, preparation of training materials for making eco enzymes and training for making eco enzymes. It is hoped that the production of this eco enzyme will have a positive impact on the lives of people throughout Sidokaton Village, Kudu District, Jombang Regency. Which will minimize budget costs and expenses. Eco enzymes have been successfully produced, which function as a natural alternative to soap and cleaners, which can be used by the public for washing dishes, cleaning floors, and other household purposes. A guide to using eco enzymes has also been prepared to help people understand how to use this product effectively and safely. This guide includes manufacturing steps, application methods, and tips for maximizing the benefits of eco enzymes in maintaining a clean home environment without using dangerous chemicals.